2019
DOI: 10.1093/ajcn/nqy254
|View full text |Cite
|
Sign up to set email alerts
|

High iron intake is associated with poor cognition among Chinese old adults and varied by weight status—a 15-y longitudinal study in 4852 adults

Abstract: Background High body iron status has been shown to be associated with adverse health outcomes. However, the relation between high body iron status, body mass index (BMI), and cognition is still understudied. Objective This study aimed to examine the association between iron intake and cognitive function in Chinese adults and tested the interaction effect of iron intake and BMI on cognition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…Our study shows that the single nutrient approach commonly used in the traditional epidemiological research can be confounded by many unmeasured factors. The current study of iron-related dietary pattern further confirms our previous findings on the association between iron intake and cognitive function [17]. The intake of iron in the fourth quartiles of IDP was 31 mg/d which is 2.5 times the recommended iron intake (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study shows that the single nutrient approach commonly used in the traditional epidemiological research can be confounded by many unmeasured factors. The current study of iron-related dietary pattern further confirms our previous findings on the association between iron intake and cognitive function [17]. The intake of iron in the fourth quartiles of IDP was 31 mg/d which is 2.5 times the recommended iron intake (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…In many countries, it has been shown that high iron levels increases the risk for diabetes [13], which is linked to cognitive impairment [14]. Despite these initial findings, the association between iron intake and cognition among older adults is inconsistent, as both positive [15, 16] and negative [17] associations have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There might exist a potential iron overconsumption among Chinese elderly. High iron intake, especially heme iron intake, and high iron store had been shown to be associated with diabetes [46,47,48], cancer [49] and cognitive impairment [50] in the Chinese population. Although dietary total iron intake among Chinese people had slightly decreased during the recent decade (from 23.3 mg/day in 2002 to 21.5 mg/day in 2012) [51], increasing dietary heme iron intake (existing only in meat and meat products) and the potential risk of iron overload, which still existed, became public health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the iron supplementation doses were within the recommended level and we did not find any health adverse outcome during the study period except for the common side effects. However, high iron levels have increased the risk of mortality and decline in cognition levels in Chinese adults [29,30]. Hence, we needed to be cautious about supplementing high doses of iron at the population level over the long-term, especially when the etiology of anemia is unknown.…”
Section: Discussionmentioning
confidence: 99%